The use of polymerase chain reaction to confirm diagnosis in skin biopsies consistent with american tegumentary leishmaniasis at histopathology: a study of 90 cases Uso da reação em cadeia da polimerase em biópsias de pele para confirmar o diagnóstico histopatológico consistente com leishmaniose tegumentar americana: um estudo de 90 casos - Rosilene Viana de Andrade; Cesare Massone; Meline Nogueira Barbosa de Lucena; Anette Chusciak Talhari; Sinésio Talhari; Jorge Augusto de Oliveira Guerra; Luiz Carlos de Lima Ferreira (Sociedade Brasileira de Dermatologia, 2011)
BACKGROUND: Cutaneous leishmaniasis is a chronic, infectious disease caused by protozoa of the genus leishmania. The incidence of this disease is high in Brazil, with 19,746 new cases having been detected in 2008. The presence of amastigotes in the cytoplasm of histiocytes constitutes diagnosis of the disease; however, their presence is rarely found in late lesions, making histological diagnosis difficult. Polymerase chain reaction has been shown to represent a highly sensitive and specific technique for the diagnosis of cutaneous leishmaniasis. OBJECTIVES: To use polymerase chain reaction to evaluate paraffin-embedded skin biopsies with histopathological features consistent with cutaneous leishmaniasis. MATERIAL AND METHODS: Polymerase chain reaction amplification of a 120-base-pair fragment of Leishmania kinetoplast DNA (kDNA) minicircles was performed on 90 skin biopsies. The male/female ratio was 75/15. Mean age was 32.36 years, with a median of 31 years, range 4-72 years. Samples were histologically compatible with cutaneous leishmaniasis but a definitive diagnosis could not be made since amastigotes were not found. All cases were histologically classified according to the patterns described by de Magalhães. RESULTS: According to the de Magalhães classification, the most common histological pattern was type IV (exudative granulomatous reaction), which was found in 65.6% of cases (56/90), followed by type I (exudative cellular reaction) in 21.1% of cases (19/90) and type III (exudative and necrotic granulomatous reaction) in 12.2% of cases (11/90). Leishmania DNA was found in 96.7% of the biopsies (87/90). CONCLUSION: Polymerase chain reaction performed by amplifying kDNA is able to confirm a diagnosis of cutaneous leishmaniasis with a high degree of sensitivity in cases in which histopathology is consistent with a diagnosis of cutaneous leishmaniasis but not definitive. FUNDAMENTOS: Cutaneous leishmaniasis is a chronic, infectious disease caused by protozoa of the genus leishmania. The incidence of this disease is high in Brazil, with 19,746 new cases having been detected in 2008. The presence of amastigotes in the cytoplasm of histiocytes constitutes diagnosis of the disease; however, their presence is rarely found in late lesions, making histological diagnosis difficult. Polymerase chain reaction has been shown to represent a highly sensitive and specific technique for the diagnosis of cutaneous leishmaniasis. OBJECTIVES: To use polymerase chain reaction to evaluate paraffin-embedded skin biopsies with histopathological features consistent with cutaneous leishmaniasis. MATERIAL AND METHODS: Polymerase chain reaction amplification of a 120-base-pair fragment of Leishmania kinetoplast DNA (kDNA) minicircles was performed on 90 skin biopsies. The male/female ratio was 75/15. Mean age was 32.36 years, with a median of 31 years, range 4-72 years. Samples were histologically compatible with cutaneous leishmaniasis but a definitive diagnosis could not be made since amastigotes were not found. All cases were histologically classified according to the patterns described by de Magalhães. RESULTS: According to the de Magalhães classification, the most common histological pattern was type IV (exudative granulomatous reaction), which was found in 65.6% of cases (56/90), followed by type I (exudative cellular reaction) in 21.1% of cases (19/90) and type III (exudative and necrotic granulomatous reaction) in 12.2% of cases (11/90). Leishmania DNA was found in 96.7% of the biopsies (87/90). CONCLUSION: Polymerase chain reaction performed by amplifying kDNA is able to confirm a diagnosis of cutaneous leishmaniasis with a high degree of sensitivity in cases in which histopathology is consistent with a diagnosis of cutaneous leishmaniasis but not definitive.